Distribution Of Diarrhea Disease In Gunungpati Public Health Center, Semarang City, 2022-2024 - Salma Bening Naffisa; Rania Reswanda; Deva Nur Febriana; Amelia Taryusri; Fadia Hilmi Aqila; Muhammad Zidan Kautsar; Kismi Mubarokah; Nur Syahidah Rahmawati; Destya Sari Widyaningrum; Helmy Grace Profita (VISIKES, 2026)
Diarrhea Still become problem health important communities, especially in developing countries . Research this aim for describe distribution disease diarrhea in the work area Community Health Center Gunungpati, Semarang City, in 2022–2024. Research This use design descriptive quantitative with utilize secondary data sources from report surveillance diarrhea, System Information Health Center, and profile health. All case recorded diarrhea during period study made into subject study with total sampling method. Data were analyzed in a way descriptive and presented in form mapping distribution based on location place stay patient and type gender. Research results show existence trend improvement case diarrhea during three year consecutively. Subdistrict Pongangan in a way consistent become an area with amount case highest in 2023 and 2024, while Ward Jatirejo take notes amount case lowest every year. Based on type gender, case diarrhea more Lots occurs in women compared to male. Findings This indicates that difference condition sanitation environment, access to clean water, and behavior life clean and healthy inter- regional contributions to variation incident diarrhea, so that effort promotive and preventive need strengthened especially in risk areas tall.